The collapse of American policy in Russia and Siberia, 1918 : Wilson's decision not to intervene (March-October, 1918) - by Victor M. Fic. (East European Monographs ; distributed by Columbia University Press, 1995)
Includes bibliographical references (p. 449-481) and index.